The Experience of Adaptation of V. Fisher’s Questionnaire «Divorce Adjustment Scale» in Kazakhstan (Хабаршы. Психология және социология сериясы, 2018)
The article presents the experience of adaptation of foreign questionnaire «Fisher Divorce Adjustment Scale» (FDAS). The substantiation of the necessity of testing the English version of the questionnaire for the Russian-speaking population, is living in Kazakhstan. This is due to primarily to the lack of this kind of instructional techniques and methods for psychodiagnosis divorced people to help them in further need of psychological help in overcoming post divorce crisis. In the conducted research an attempt is made to overcome the existing situation regarding the lack of necessary psychodiagnostic methods and methods for working with divorced people. To this end, we carried out work on the testing of the FDAS questionnaire in accordance with all requirements for the reliability and validity of the psychodiagnostic toolkit. Considers the organizational aspects of the Russian version of the test in compliance with the requirements of appropriate testing it was translated into the Russian language techniques. Describes how to create a traditional primary forms of the questionnaire and its psychometric test. First of all, a detailed description of the procedure for the initial translation of the test from the original language into Russian, the verification of the equivalence of the translation, and the meaningful evaluation of the translation are given. Analyzes the reasons for the low efficiency of the statements identified after analysis of the items, as well as some aspects of performance of psychometric characteristics of test.Key words: divorce, adjusting to divorce, testing questionnaire.